Consumer Acceptance of Biscuits Supplemented with a Sorghum–Insect Meal - Awobusuyi, Temitope D. (Nutrients, 2020)
Insects are abundant in the predominantly sub-Saharan Africa region and are generally high in protein. Wheat grain contains gluten that is vital for the quality of baked goods but does not grow well in warm regions. Partial substitution of wheat with sorghum and insect in biscuits could contribute to food security among vulnerable populations. This study identified insect types most commonly consumed by the rural Olugboja community living in the rural part of the Ikare-Akoko local government area of Ondo State, Nigeria and consumer acceptance of biscuits supplemented with a sorghum and insect meal. Whole grain sorghum meal and insect meal were blended at a ratio of 3:1 (w/w sorghum: insect). Composite biscuits were made by partially substituting wheat flour with the sorghum–insect meal at 20%, 40%, and 60% (w/w). Wheat biscuit (100%) was used as a control. Regular consumers of biscuits (n = 84) evaluated the acceptability of the biscuit samples using a five-point facial hedonic scale, which was followed by focus group discussions (FGDs) to assess consumer perceptions of the use of insect as a food source. Biscuits containing the sorghum–insect meal (mean = 4.0 ± 0.6) were more acceptable than the control (3.58 ± 0.6). The biscuits supplemented with 20% of the sorghum–insect meal were the most acceptable (mean = 4.23 ± 0.6) compared to those with higher concentrations (40% and 60%). FGDs revealed that the taste of the biscuits was an important motivation for consumers to accept insect as a food source.